Mass-loss of massive helium star supernova progenitors shortly before explosion constrained by supernova radio properties. Issue 4 (7th May 2022) - Moriya, Takashi J; Yoon, Sung-Chul
ABSTRACT: Mass-loss of massive helium stars is not well understood even though it plays an essential role in determining their remnant neutron-star or black hole masses as well as ejecta mass of Type Ibc supernovae (SNe Ibc). Radio emission from SNe Ibc is strongly affected by circumstellar matter properties formed by mass-loss of their massive helium star progenitors. In this study, we estimate the rise time and peak luminosity distributions of SNe Ibc in radio based on a few massive helium star mass-loss prescriptions and compare them with the observed distribution to constrain the uncertain massive helium star mass-loss rates. We find that massive helium stars in the luminosity range expected for ordinary SNe Ibc progenitors (4.6 ≲ log L /L⊙ ≲ 5.2) should generally have large mass-loss rates (≳ 10 −6 M⊙ yr −1 ) in order to account for the observed rise time and peak luminosity distribution. Therefore, mass-loss prescriptions that predict significantly low mass-loss rates for helium stars in this luminosity range is inconsistent with the SN radio observations. It is also possible that massive helium stars shortly before their explosion generally undergo mass-loss enhancement in a different way from the standard radiation-driven wind mechanism.